THE EFFECTIVENESS OF FORECASTING IN EMERGENCY SITUATIONS - Akhmadbek Jalilov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article examines the effectiveness of forecasting in emergency situations (ES). Using the example of Uzbekistan, the benefits of early detection of hazards such as earthquakes and floods are examined. The study shows that forecasting systems saved 5,000 lives and prevented 300 million soums of damage. At the same time, it was found that early warning helped evacuate 1,000 people. The article emphasizes the importance of forecasting to strengthen preparedness for ES and protect infrastructure. The study is based on international experience and local data. Although the lack of real-world testing is noted as a limitation, suggestions are made for future development of the systems. This work reveals the value of forecasting for ensuring security and increasing economic stability.